The effect of foliar feeding with organic fertilizer "Orgomin" and seaweed extract "Amino food" on some indicators of vegetative growth and nodes of apple cultivar "Golden delicious". - صالح, زينب; جرجس مخول , (Latakia University Journal -Biological Sciences Series, 2023)
The research was carried out during the 2022 season on apple trees of the “Golden delicious” variety in the Kasab region of Lattakia Governorate, at an altitude of 800 m above sea level. food" in the area of the leaf blade and its content of total chlorophyll, the percentage of flower nodes, and the percentage of fallen fruits. The trial was designed by the completely randomized method; The number of experimental treatments was (9), and the results were analyzed using the Genstat12 computer program, using the Duncan test, and calculating the LSR value at 5% for field studies and 1% for laboratory analyzes to determine the significant differences between the treatments. - The results of the study showed that the two treatments (Orgomin 2 cm3/liter + 2 cm3/liter Amino food) and (Orgomin 2 cm3/liter + Amino food 1 cm3/liter) in terms of the percentage of knotted flowers were superior to all other treatments with a contraction rate of (68.23% and 67.21%) without a significant difference between them; While it was in the witness (38.80%). Foliar feeding treatments greatly reduced the percentage of fruit falling after setting, and it was the lowest in the treatment (2 cm3/liter Orgomin + 2 cm3/liter Amino food) (46.85%) and the highest in the control (62.79%). -The results of the study showed that the treatment (2 cm3 / liter Orgomin + 2 cm3 / liter Amino food) gave the highest value for the leaf blade area (35.45 cm2), followed by the treatment (2 cm3 / liter Orgomin + 1 cm3 / liter Amino food) (32.03 cm2), and from Then the treatment (2 cm3 / liter Amino food) was (31.84 cm2), while the least area of the leaf blade in the control was (26.82 cm2). The results of the statistical analysis showed the superiority of the treatment (2 cm3 / liter Orgomin + 2 cm3 / liter Amino food), the treatment (2 cm3 / liter Orgomin + 1 cm3 / liter Amino food), and the treatment (2 cm3 / liter Amino food) over the rest of the treatments, including the control without There is a significant difference between them. As for the total chlorophyll content of the leaves, the treatment (2 cm3 / liter Orgomin + 2 cm3 / liter Amino food) gave the highest value (62.98 SPAD); While it was the lowest in the witness papers (52.99 SPAD). All treatments were superior to the control without a significant difference between them, except for the treatment (1 cm3 / liter Amino food).